Recognizing local people’s priorities for tropical forest biodiversity - Sheil, Douglas; Puri, R.K.; Wan, M.; Basuki, I.; Heist, M. van; Liswanti, N.; Rukmiyati; Rachmatika, I.; Samsoedin, I. (2006)
Tropical forest people often suffer from the same processes that threaten biodiversity. An improved knowledge of what is important to local people could improve decision making. This article examines the usefulness of explicitly asking what is important to local people. Our examples draw on biodiversity surveys in East Kalimantan (Indonesian Borneo). With local communities we characterized locally valued habitats, species, and sites, and their significance. This process clarified various priorities and threats, suggested refinements and limits to management options, and indicated issues requiring specific actions, further investigation, or both. It also shows how biological evaluations are more efficient with local guidance, and reveals potential for collaborations between local communities and those concerned with conservation. Such evaluations are a first step in facilitating the incorporation of local concerns into higher-level decision making. Conservationists who engage with local views can benefit from an expanded constituency, and from new opportunities for pursuing effective conservation.